Refractory cardiogenic shock in hypertrophic cardiomyopathy complicated by apical ballooning: A case report - Matej Strycek; Rostislav Polasek; Pavol Tomasov; Jiri Karasek (Journal of International Medical Research)
Hypertrophic cardiomyopathy can be accompanied by dynamic obstruction in the left ventricular outflow tract and acute apical ballooning, which are among the very rare causes of cardiogenic shock. This condition requires a specific treatment approach that in many ways differs from the treatment of other causes of cardiogenic shock. We present a case and our treatment strategy (including extracorporeal life support) for refractory cardiogenic shock in a patient with previously undiagnosed hypertrophic cardiomyopathy.